2018
DOI: 10.1063/1.5001708
|View full text |Cite
|
Sign up to set email alerts
|

Modular portable unit for thermal conductivity measurements in multiple cryogenic/magnetic field environments

Abstract: A modular design for a miniature thermal conductivity cell suitable for a dilution refrigerator and other sample-in-vacuum cryogenic environments with different magnet options is described. The sample is mounted once and the contacts remain in place when the unit is repositioned or transported between different magnets and cryostats. This mobility enables comprehensive measurements with access to specific options, such as vector magnet in one lab and ultra-high field in another. This design enables significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Laue diffraction confirmed that the samples were high-quality single crystals ( Figure S6). Thermal conductivity measurements were performed using modular thermal conductivity (MTC) setups, [20] enabling measurements in several cryogenic environments, a cryogen-free He3 setup (0.5 to 3 K) and the high-vacuum option of a PPMS (above 2 K), without sample dismounting. A standard one-heater-two-thermometers technique was used for thermal conductivity measurements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Laue diffraction confirmed that the samples were high-quality single crystals ( Figure S6). Thermal conductivity measurements were performed using modular thermal conductivity (MTC) setups, [20] enabling measurements in several cryogenic environments, a cryogen-free He3 setup (0.5 to 3 K) and the high-vacuum option of a PPMS (above 2 K), without sample dismounting. A standard one-heater-two-thermometers technique was used for thermal conductivity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The first MTC setup utilized RuO2 thermometers and was constructed for measurements in the temperature range 0.02 to 40 K. The second setup used Cernox 1030 thermometers, suitable for measurements from 0.3 to 300 K. The calibration of the modular thermal conductivity setup with RuO2 thermometers was described elsewhere. [20] The design with Cernox 1030 thermometers was specially built to study the properties of BaNi2P4 at elevated temperatures. This device was tested using measurements of standard Ag wire as shown in the supplementary material ( Figure S4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contacts for thermal transport measurements were made by soldering gold wire leads to evaporated gold pads using an In-Sn alloy, resulting in ∼mΩ contact resistances. Thermal transport was measured in a dilution refrigerator (DR) using a modular one-heater, two-thermometer probe [10], and heat capacity measured using the relaxation time method. As discussed below, the observation of the WF law in the field-induced normal state rules out electron-phonon decoupling issues [11].…”
mentioning
confidence: 99%